Jumanji: 2-movie collection [videorecording (Blu-Ray)] : Jumanji: the next level ; Jumanji: welcome to the jungle. - Jackman, Henry (Henry Pryce) (Sony Pictures Home Entertainment, 2020)
Jumanji. Welcome to the jungle: Four high school kids discover an old video game console and are drawn into the game's jungle setting, literally becoming the adult avatars they chose.